Postmortem clots (PMC) of the heart; is it merely an artifact or a predictor of cause of death? - Senanayake, Kumara; Amerasinghe, Ishanka; Warnasekara, Janith (Ceylon medical journal, 2022)
Post Mortem Clots (PMC) are considered as artifacts observed during forensic autopsies; hence, their medico legal importance has not been evaluated at length in the past. This study was designed with the intent of finding the association of age, gender, cause of death (COD) and postmortem interval (PI) with PMC formation.BackgroundPost Mortem Clots (PMC) are considered as artifacts observed during forensic autopsies; hence, their medico legal importance has not been evaluated at length in the past. This study was designed with the intent of finding the association of age, gender, cause of death (COD) and postmortem interval (PI) with PMC formation.Secondary data of all postmortems performed by the 1st author from June,2015 to June,2018 at Teaching Hospital Anuradhapura were extracted. Eligible autopsies were evaluated for the presence of PMCs in the heart. Length of the PMCs present was quantified as a percentage of the length of the cardiac chambers. Presence of PMCs varied according to the COD which were clustered based on their mechanism of death.MethodsSecondary data of all postmortems performed by the 1st author from June,2015 to June,2018 at Teaching Hospital Anuradhapura were extracted. Eligible autopsies were evaluated for the presence of PMCs in the heart. Length of the PMCs present was quantified as a percentage of the length of the cardiac chambers. Presence of PMCs varied according to the COD which were clustered based on their mechanism of death.The study evaluated 1259 autopsies with a median age of 56 years (IQR 40-67). PMCs were found in 46% of the subjects and showed a female predominance. The percentage of length of PMCs ranged from 20% to 100%. A higher rate of PMC formation was observed in natural and infectious causes, especially in the elderly. Traumatic causes with multiple injuries, heavy bleeding and a short agonal period showed less tendency of PMC formation. A higher duration of hospital stay/injury to death (> 90 h) was associated with formation of PMC. PMC is not associated with PI while it's associated with increased age.ResultsThe study evaluated 1259 autopsies with a median age of 56 years (IQR 40-67). PMCs were found in 46% of the subjects and showed a female predominance. The percentage of length of PMCs ranged from 20% to 100%. A higher rate of PMC formation was observed in natural and infectious causes, especially in the elderly. Traumatic causes with multiple injuries, heavy bleeding and a short agonal period showed less tendency of PMC formation. A higher duration of hospital stay/injury to death (> 90 h) was associated with formation of PMC. PMC is not associated with PI while it's associated with increased age.PMC is not a mere artifact but has significant medicolegal importance with regards to COD and time from injury to death.ConclusionPMC is not a mere artifact but has significant medicolegal importance with regards to COD and time from injury to death.